Preparation and characterization of natural rubber with soft nanomatrix structure - Kenichiro Kosugi (2018)
Abstract Preparation of natural rubber (NR) with a soft nanomatrix structure was made by graft-copolymerization of butyl acrylate (BA) onto deproteinized natural rubber with tert-butyl hydroperoxide/tetraetylenepentamine in latex stage. The resulting graft-copolymer of deproteinized natural rubber and poly (butyl acrylate) (DPNR-graft-PBA) was characterized by Fourier-transforminfrared spectroscopy. Conversion and grafting efficiency of BA were dependent upon BA concentration, which were more than 90 mol% under a suitable condition of the graft-copolymerization. Morphology of DPNR-graft-PBA was observed by transmission electron microscopy after staining film specimens with I2 vapor for 5min. TheNR particles of about 0.5 μm in diameter were dispersed in PBA matrix of about 15 nm in thickness. Storage modulus and loss tangent of DPNR-graft-PBA were measured, and they were related with the soft nanomatrix structure. The tensile strength and elongation at break decreased as monomer concentration increased. © Springer-Verlag 2012.